2013
DOI: 10.1371/journal.pone.0071640
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 Ile105Val Polymorphism and Prostate Cancer Risk: Evidence from a Meta-Analysis

Abstract: BackgroundGlutathione S-transferase P1 (GSTP1) is thought to be involved in the detoxification of reactive carcinogen metabolites. Numerous epidemiological studies have evaluated the association of GSTP1 Ile105Val polymorphism with the risk of prostate cancer. However, the results remain inconclusive. To derive a more precise estimation, a meta-analysis was performed.Methodology/Principal FindingsA comprehensive search was conducted to identify the eligible studies. We used odds ratios (ORs) with 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Another study by Aynacioglu et al (2004) reported that the Val/Val homozygous genotype appeared to be somewhat protective against developing asthma compared to the other two genotypes (Aynacioglu, Nacak, Filiz, Ekinci, & Roots, 2004). A recessive model of GSTP1 was used in a study by Wei et al (Wei et al, 2013), where a significant association was found for low-stage prostate cancer in a meta-analysis. A dominant model was considered by Chen et al (2010) and a significant association of GSTP1 with hepatocellular carcinoma was observed (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study by Aynacioglu et al (2004) reported that the Val/Val homozygous genotype appeared to be somewhat protective against developing asthma compared to the other two genotypes (Aynacioglu, Nacak, Filiz, Ekinci, & Roots, 2004). A recessive model of GSTP1 was used in a study by Wei et al (Wei et al, 2013), where a significant association was found for low-stage prostate cancer in a meta-analysis. A dominant model was considered by Chen et al (2010) and a significant association of GSTP1 with hepatocellular carcinoma was observed (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the GST family subgroup genes, including GST mu 1 ( GSTM1 ), GST pi 1 ( GSTP1 ), and GST theta 1 ( GSTT1 ), are highly polymorphic (Loktionov et al, 2001). Sequence variation in these genes has also been associated with an increased or decreased risk for several cancers and chronic diseases, including colorectal cancer (Loktionov et al, 2001), esophageal cancer (Sharma et al, 2013), renal cell carcinoma (Cheng, You, & Zhou, 2012; Yang et al, 2013), acute leukemia (Ye & Song, 2005), prostate cancer (Harries, Stubbins, Forman, Howard, & Wolf, 1997; Kote-Jarai et al, 2001; Liu, Liu, Ran, Shang, & Li, 2013; Safarinejad, Shafiei, & Safarinejad, 2011; Taioli et al, 2011; Wei et al, 2013), type-2 diabetes mellitus (Dadbinpour, Sheikhha, Darbouy, & Afkhami-Ardekani, 2013; Ramprasath et al, 2011), asthma (Tamer et al, 2004), and neurodevelopmental disorders such as ASD (Buyske et al, 2006). The variants in GSTM1 and GSTT1 examined here are insertion-deletion polymorphisms, and the homozygous deletions or null genotypes indicate that activities or functionality of these genes are reduced or interrupted completely (Ye, Song, Higgins, Pharoah, & Danesh, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have confirmed that those who express different types of GSTP1 alleles are less susceptible to various types of carcinogenic agents (Josephy, 2010;Andreoli and Sprovieri, 2017). Recent studies have reported the relation between GSTP1 Val105 polymorphism and other types of cancers, including prostate (Wei et al, 2013), breast (Louie et al, 2016), and bladder cancers (Yu et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
“…In general, individuals with the CYP2E1 C1/C1 genotype, slow acetylator NAT2 genotype, or GSTM1 null genotype have been shown to have an increased risk of ADLI [ 20 , 21 ]. In addition, studies have shown the Ile105Val and MspI polymorphisms in GSTP1 and CYP1A1 , respectively, with mutant genotypes likely reducing the activities of the respective genes [ 22 , 23 ]. However, we found GSTP1 and CYP1A1 polymorphisms to be unrelated to increased risk of ADLI.…”
Section: Discussionmentioning
confidence: 99%